PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN APLIKASI CANVA PADA MATERI BANGUN DATAR DI KELAS V UPTD SD NEGERI 6 KUTA BLANG - Nashrina; Rahmi Wahyuni; Fachrurazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematical problem-solving ability of fifth-grade students of UPTD SD Negeri 6 Kuta Blang, especially on the material of plane figures. To overcome this problem, researchers implemented the Problem Based Learning (PBL) model assisted by the Canva application as an effort to improve the quality of learning. This study aims to determine the improvement of students' mathematical problem-solving abilities, teacher and student activities during the learning process, and student responses to the application of the learning model. The type of research used is Classroom Action Research (CAR) with an approach. The subjects of this study were 17 fifth-grade students of UPTD SD Negeri 6 Kuta Blang. Research data were collected through tests, observations, and questionnaires, then analyzed using the percentage of completeness technique. The results of the study showed an increase in students' mathematical problem-solving abilities. The percentage of learning completeness in cycle I was 47.05%, increasing to 94.11% in cycle II, with an increase of 47.06%. Teacher activity increased from 82.72% in cycle I to 96.36%, while student activity increased from 85.45% to 96.31%. Student response to the implementation of the Problem Based Learning model assisted by the Canva application was categorized as very good. Thus, this study shows that the implementation of the Problem Based Learning model assisted by the Canva application can improve the mathematical problem-solving abilities of fifth-grade students on the topic of plane figures at the UPTD of SD Negeri 6 Kuta Blang. The results of this study can be an alternative for teachers in selecting effective learning models and media to improve students' mathematical problem-solving abilities in elementary schools.